2018
DOI: 10.1038/s41416-018-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to overhead power lines and childhood leukaemia: an international pooled analysis

Abstract: In this first comprehensive pooled analysis of childhood leukaemia and distance to power lines, we found a small and imprecise risk for residences < 50 m of 200 + kV lines that was not explained by high magnetic fields. Reasons for the increased risk, found in this and many other studies, remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Similarly, dwelling type did not affect a previously observed multiplicative interaction between calculated fields and distance [30], although numbers were small. These observations were consistent with previous findings for dwelling type in pooled analyses [14,15]. Our results were slightly higher for proximity to power lines (OR 1.50) and slightly lower for the highest calculated fields (OR 1.39) due to the dwelling sample subset compared with previous studies [31,32].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, dwelling type did not affect a previously observed multiplicative interaction between calculated fields and distance [30], although numbers were small. These observations were consistent with previous findings for dwelling type in pooled analyses [14,15]. Our results were slightly higher for proximity to power lines (OR 1.50) and slightly lower for the highest calculated fields (OR 1.39) due to the dwelling sample subset compared with previous studies [31,32].…”
supporting
confidence: 92%
“…Being merely associated with MF exposures and leukemia would not qualify dwelling type as a confounder [12], in which case it could be a collider in an M-bias structure [13]. While two pooled analyses did not show dwelling type to be a confounder in the MF-leukemia relationship [14,15], residence type has been shown to be a strong predictor of measured magnetic fields [16]. Several studies have found greater exposure to magnetic fields in apartments when using both measurements [2,[17][18][19][20] and calculations [6].…”
Section: Introductionmentioning
confidence: 99%
“…2011, 2015), passive smoking (Metayer et al. 2016b; Pyatt and Hays 2010), magnetic field exposure (Amoon et al. 2018), and socioeconomic factors (Kehm et al.…”
Section: Discussionmentioning
confidence: 99%
“…2016a). In addition to established and putative environmental risk factors such as ionizing and nonionizing radiation (Amoon et al. 2018; Bartley et al.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of childhood cancer in relation to proximity to pollution foci have reached great importance recently [2227], and industrial registers of toxic substances as the E-PRTR provide a tool for the monitoring and surveillance of harmful effects of these industrial pollutants, some of them carcinogenic, on the human health. In this sense, our experience is being positive because our study is providing some epidemiological clues that residing in the vicinity of certain industrial and urban areas may be a risk factor for some types of childhood cancers.…”
Section: Discussionmentioning
confidence: 99%